АНОРМАЛЬНІ РЕЗОНАНСНІ ПЕРЕНАПРУГИ В МАГІСТРАЛЬНИХ ЕЛЕКТРИЧНИХ МЕРЕЖАХ З ДЖЕРЕЛАМИ СПОТВОРЕНЬ - Кучанский, В.В. (Інститут електродинаміки Національної академії наук України, 2018)
The paper deals with the analysis and classification of durable internal overvoltages in the main power electrical network. The work considers the possibility of developing overvoltages in abnormal modes with sources characterized by distortions: asymmetric, nonsinusoidal and combined. Investigated those abnormal resonance overvoltages which occur in the extra high voltage transmission lines 750 kV with nonsinusoidal and asymmetric sources of distortion depend of many interconnected processes and on the values of a large number of parameters. Such an overvoltage classification is not accidental, since the source of their occurrence and distortion characteristics determine an abnormal regime. Described an example of such distortion, is incomplete mode of operation of the extra-high voltage transmission line, which causes the appearance of resonance circuits with distributed capacities of the line and the inductances of the shunt reactors. Detected that the second type of abnormal resonance overvoltages occur when extra high voltage transmission line switching on to no-loaded autotransformer. The theoretical principles of the emergence of harmonic resonant overvoltages with the inclusion of the superconducting voltage on the unloaded autotransformer are given. The key factor which led to abnormal nonsinusoidal mode is saturation magnetical core of noloaded autotransformer is analyzed. The main approaches to the study of abnormal resonance overvoltages are described and directions of the subsequent researches are designated. The obtained results of the research indicate the expediency of studying the conditions of occurrence and existence of abnormal resonance overvoltages. Bibl. 15, fig. 5, table.